DIFICULTADES EN LA SUPERACIÓN DE ERRORES CONCEPTUALES RELACIONADOS CON EL APRENDIZAJE DEL EQUILIBRIO QUÍMICO EN ALUMNOS UNIVERSITARIOS (2013)
One problem for classroom teachers is that the methods traditionally used to identify student altemative conceptions are extreme! y time consurning. On the other hand, che mi cal equilibrium misconceptions, which most of them are related with the prediction of chemical equilibrium shift, are tenacious and resistant to extinction. In this work I present a simple methodology developed to provide teachers with an easily administered and evaluated test, designed to identify students altemative conceptions specially those related with the erroneous application of the Le Chatelier Principie in systems that has been perturbed by the addition of a so lid ora inert gasto the equilibrium mixture. The test was adrninistrated to two groups of university students of different leve! of instruction. The results obtained are in agreement with the general statement that this students misconceptions are difficult of overcoming even for advanced students